ROLE OF MICROFINANCE INSTITUTIONS IN FINANCIAL INCLUSION IN INDIA - Sharma, Dr. Aastha; Sharma, Dr. Megha; Awasthi, Mr. Gunwant; Poojari, Ms. Lata (The journal of contemporary issues in business and government, 2023)
Financial inclusion is emerging as a new paradigm of economic growth that plays major role in driving away the poverty from the country. Banking services are making accessible to masses including privileged and disadvantaged people at an affordable terms and conditions. But a section of the society in developing economy still deprived of financial services. Microfinance institutions plays a very significant role in bridging the gap. Financial inclusion is important priority of the country in terms of economic growth and advanceness of society. It enables to reduce the gap between rich and poor population. In the current scenario financial institutions are the robust pillars of progress, economic growth and development of the economy. The present study aims to examine Microfinance impact on financial inclusion in the economy. Secondary data has been taken for analysing the impact of microfinance institutions in India. Results of the study found positive and there is significant impact of Microfinance institutions on financial inclusion aspect.